ICT and teacher training - Montejo Garzón, Katherine Johana
The exponential advance of ICT in recent decades has generated that these tools are increasingly part of the lives of people. Education must not be alien to this fact, is through it that a technological culture must be developed where people are able to interact with technology and integrate it into everyday actions, giving it meaning as an instrument of knowledge production and socialization. To achieve this, it is necessary to train future teachers, not only in the use of ICT, but also in their integration into the classroom, as suggested by the different ICT competencies for teacher training.